Adapting to the impact of COVID-19: Sharing stories, sharing practice. (2nd July 2020) - Cleland, Jennifer; McKimm, Judy; Fuller, Richard; Taylor, David; Janczukowicz, Janusz; Gibbs, Trevor
Abstract: Health Professions' Educators (HPEs) and their learners have to adapt their educational provision to rapidly changing and uncertain circumstances linked to the COVID-19 pandemic. This paper reports on an AMEE-hosted webinar: Adapting to the impact of COVID-19: Sharing stories, sharing practice . Attended by over 500 colleagues from five continents, this webinar focused on the impact of the virus across the continuum of education and training. Short formal presentations on teaching and learning, assessment, selection and postgraduate training generated wide-ranging questions via the Chatbox. A thematic analysis of the Chatbox thread indicated the most pressing concerns and challenges educators were experiencing in having to adapt programmes and learning across the continuum of medical education and training. The main areas of concern were: campus-based teaching and learning; clinical teaching; selection and assessment, and educator needs. While there is clearly no one simple solution to the unprecedented issues medical education and training face currently, there were two over-arching messages. First, this is a time for colleagues across the globe to help and support each other. Second, many local responses and innovations could have the potential to change the shape of medical education and training in the future.